Comportamentos reológicos de materiais macios usando modelagem no contínuo - Costa, Damião Ferreira da Silva (2024)
This work presents an investigation into the rheological behavior of soft materials using the continuum approach and numerical simulation techniques through the Finite Element Method (FEM). The research was divided into two main parts: the first focused on nanoindentation tests to evaluate the finite size effect and the influence of substrate stiffness on the measurement of the elastic properties of viscoelastic and elastic samples. Three indenter geometries (conical, spherical, and cylindrical) were considered, indicating that the conical indenter provides more robust measurements, especially when analyzing variations in sample height and substrate stiffness. The second part of the study explored the influence of fractal surfaces, specifically the Koch curve, on determining the Young's modulus of elastic materials. Samples with fractal surfaces were simulated under two different configurations, referred to as Up and Down. The results showed that the presence of fractal surfaces can increase or decrease the obtained Young's modulus, especially in thinner samples that have fractal surfaces in the Up orientation. Additionally, it was observed that although stiffness and Young's modulus decrease with the increase in the sample's base length L, the influence of fractality remains constant. FEM is an effective tool for the numerical modeling of soft materials, allowing for detailed analysis of finite-size effects and surface complexity on the mechanical properties of such materials. This study provides important insights for experiment design and result interpretation in contexts where complex and rough surfaces are present. For future work, it is suggested that the simulations be expanded to three-dimensional geometries and phenomena such as drag force in deformable solids immersed in fluids be investigated.